Soil and crop response to stover removal from rainfed and irrigated corn. Issue 2 (31st October 2013) - Kenney, Ian; Blanco‐Canqui, Humberto; Presley, Deann R.; Rice, Charles W.; Janssen, Keith; Olson, Brian
Abstract Excessive corn (Zea mays L.) stover removal for biofuel and other uses may adversely impact soil and crop production. We assessed the effects of stover removal at 0, 25, 50, 75, and 100% from continuous corn on water erosion, corn yield, and related soil properties during a 3‐year study under irrigated and no‐tillage management practice on a Ulysses silt loam at Colby, irrigated and strip till management practice on a Hugoton loam at Hugoton, and rainfed and no‐tillage management practice on a Woodson silt loam at Ottawa in Kansas, USA. The slope of each soil was <1%. One year after removal, complete (100%) stover removal resulted in increased losses of sediment by 0.36–0.47 Mg ha−1 at the irrigated sites, but, at the rainfed site, removal at rates as low as 50% resulted in increased sediment loss by 0.30 Mg ha−1 and sediment‐associated carbon (C) by 0.29 kg ha−1. Complete stover removal reduced wet aggregate stability of the soil at the irrigated sites in the first year after removal, but, at the rainfed site, wet aggregate stability was reduced in all years. Stover removal at rates ≥ 50% resulted in reduced soil water content, increased soil temperature in summer by 3.5–6.8 °C, and reduced temperature in winter by about 0.5 °C. Soil C pool tended to decrease and crop yields tended to increase with an increase in stover removal, but 3 years after removal, differences were not significant. Overall, stover removal at rates ≥50% may enhance grain yield but may increase risks of water erosion and negatively affect soil water and temperature regimes in this region.